'GEOGRAPHICAL INDICATION'AS A STRATEGY FOR MARKETING OF HANDLOOM PRODUCTS: EVIDENCE FROM SAREE INDUSTRY - N. D., Divya; Kumar, Dr. N. Ajith (The journal of contemporary issues in business and government, 2023)
Geographic indication of goods, a part of intellectual property rights, identifies the location of a commodity. Various categories may be used to categorise these things, such as agricultural, natural commodities, manufactured goods, food items, textiles, and handicrafts. Sarees are one of the nation's more well-known and pricey handcrafted goods. The current study intends to investigate the market potential and efficiency of the Indian handloom saree business. The product comparison demonstrates that every brand has its own marketing plan. Additionally, the prices of these sarees vary widely between brands and are not uniform.